Android security cookbook : practical recipes to delve into Android's security mechanisms by troubleshooting common vulnerabilities in applications and Android OS versions /: practical recipes to delve into Android's security mechanisms by troubleshooting common vulnerabilities in applications and Android OS versions. (2013) - Unknown
No abstract available